NSAIDs, Mitochondria and Calcium Signaling: Special Focus on Aspirin/Salicylates - Yoshihiro Suzuki; Toshio Inoue; Chisei Ra (MDPI AG, 2010)
Aspirin (acetylsalicylic acid) is a well-known nonsteroidal anti-inflammatory drug (NSAID) that has long been used as an anti-pyretic and analgesic drug. Recently, much attention has been paid to the chemopreventive and apoptosis-inducing effects of NSAIDs in cancer cells. These effects have been thought to be primarily attributed to the inhibition of cyclooxygenase activity and prostaglandin synthesis. However, recent studies have demonstrated unequivocally that certain NSAIDs, including aspirin and its metabolite salicylic acid, exert their anti-inflammatory and chemopreventive effects independently of cyclooxygenase activity and prostaglandin synthesis inhibition. It is becoming increasingly evident that two potential common targets of NSAIDs are mitochondria and the Ca2+ signaling pathway. In this review, we provide an overview of the current knowledge regarding the roles of mitochondria and Ca2+ in the apoptosis-inducing effects as well as some side effects of aspirin, salicylates and other NSAIDs, and introducing the emerging role of L-type Ca2+ channels, a new Ca2+ entry pathway in non-excitable cells that is up-regulated in human cancer cells.